Relative clause reading in hearing impairment: different profiles of syntactic impairment - Szterman, Ronit; Friedmann, Naama (Frontiers in Psychology, 2014)
Children with hearing impairment show difficulties in sentences derived by Wh-movement, such as relative clauses and Wh-questions. This study examines the nature of this deficit in 48 hearing impaired children aged 9-12 years and 38 hearing controls. The task involved reading aloud and paraphrasing of object relatives that include a noun-verb heterophonic homograph. The correct pronunciation of the homograph in these sentences depended upon the correct construction of the syntactic structure of the sentence. An analysis of the reading and paraphrasing of each participant exposed two different patterns of syntactic impairment. Some hearing-impaired children paraphrased the object relatives incorrectly but could still read the homograph, indicating impaired assignment of thematic roles alongside good syntactic structure building; other hearing-impaired children could neither read the homograph nor paraphrase the sentence, indicating a structural deficit in the syntactic tree. Further testing of these children confirmed the different impairments: some are impaired only in Wh-movement, whereas others have CP impairment. The syntactic impairment correlated with whether or not a hearing device was fitted by the age of one year, but not with the type of hearing device or the depth of hearing loss: children who had a hearing device fitted during the first year of life had better syntactic abilities than children whose hearing devices were fitted later.